Is Subsidizing Inefficient Bidders Actually Costly? - Rothkopf, Michael H.; Harstad, Ronald M.; Fu, Yuhong (Management Science, 2003)
A widespread practice, particularly in public-sector procurement and dispersal, is to subsidize a class of competitors believed to be at an economic disadvantage. Arguments for such policies vary, but they typically assume that benefits of subsidization must be large enough to outweigh a presumed economic cost of the subsidy. When disadvantaged competitors compete in auctions, the subsidy serves to make them more competitive rivals. Other bidders rationally respond by bidding more aggressively. We consider a model of procurement auctions and show that a policy of subsidizing inefficient competitors can lower expected project cost and also enhance economic efficiency. Some subsidy is generally better than no subsidy for a wide range of parameters.